Concentrations of dissolved dimethyl sulfide (DMS), methanethiol and other trace gases in context of microbial communities from the temperate Atlantic to the Arctic Ocean ... - Wietz, Matthias; Gros, Valérie; Bonsang, Bernard; Sarda-Estève, Roland; Nikolopoulos, Anna; Metfies, Katja; Peeken, Ilka (Zenodo, 2023)
This archive contains bioinformatic code and data files to reproduce bacterial analyses from Gros et al. (Biogeosciences; https://doi.org/10.5194/bg-2022-150). In this study, seawater samples collected along an Atlantic-Arctic transect (55-80°N) were evaluated for microbial community composition and trace gas concentrations. Microbes were sampled underway using "AUTOFIM" automatic filtration; and bacterial communities amplicon-sequenced using 16S rRNA gene primers. Raw sequence data is available at ENA under BioProject PRJEB50492. The archive contains: - Rmarkdown for primer-clipping, ASV generation and taxonomy assignment: 1_DADA.Rmd - Rscript for ASV and metadata processing; alpha-diversity calculations: 2_DataLoad.R - Rscript for generation of manuscript figures: 3_Results.R - Rscript for generation of supplementary figures: 4_Supplement.R - Metadata and environmental parameters as .txt files ...